Inspiration by Pop-up Advertising among the Community in Batam and Consumer - Jefry Tan; Diny Anggriani Adnas (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The rapid increase in the use of Information and Communication Technology (ICT) in society has affected significant changes in entertainment media specifically in the field of video games. Advertisements in video games can influence user behavior, particularly in Inspired-To. In order to learn more about Inspired-To and how it can influence the behavior of video game players, the author will administer a questionnaire (N=390) and conduct interviews (N=30) with video game players. The authors of this study discovered that users were contented with the results of pop-up advertisements if the content was entertaining and provided incentives. The author also notes that each of the advertisements is entertaining and that providing incentive benefits can enhance the value of the advertisement. The author discovers that a strong ad value can inspire users to discover something new, which will then inspire them to download the new game advertised by the pop-up ad. This research will assist users in identifying factors that increase the likelihood that they will acquire a new game.